If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -8 = 1 + 5y + -36 Reorder the terms: -8 + 4y = 1 + 5y + -36 Reorder the terms: -8 + 4y = 1 + -36 + 5y Combine like terms: 1 + -36 = -35 -8 + 4y = -35 + 5y Solving -8 + 4y = -35 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -8 + 4y + -5y = -35 + 5y + -5y Combine like terms: 4y + -5y = -1y -8 + -1y = -35 + 5y + -5y Combine like terms: 5y + -5y = 0 -8 + -1y = -35 + 0 -8 + -1y = -35 Add '8' to each side of the equation. -8 + 8 + -1y = -35 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = -35 + 8 -1y = -35 + 8 Combine like terms: -35 + 8 = -27 -1y = -27 Divide each side by '-1'. y = 27 Simplifying y = 27
| Ax+cx=b | | 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= | | P=r+s-p | | x^2+36x+27= | | 4a^2-12a-7=0 | | 6-2*7=4x-6x-3 | | 10y+(3y+11)=180 | | 18-6a=12 | | 0=x+7-32 | | 35.00+0.75x=20 |